Application of polyoxometalate derivatives in rechargeable batteries. Issue 9 (19th February 2020) - Huang, Bo; Yang, Dong-Hui; Han, Bao-Hang
Abstract : Various polyoxometalate-derived transition metal composites can be applied as electrode materials in multiple rechargeable batteries with excellent electrochemical performances. Abstract : Early transition metal (such as Mo, W, and V) based materials are promising candidates for electrochemical rechargeable batteries on account of their high valence state, unique crystal structures, and thermal stability. In this case, as a kind of well-defined inorganic nanocluster composed of early transition metals and oxygen atoms, polyoxometalates (POMs) are appropriate precursors to generate such emerging early transition metal based electrode materials. Benefiting from the inherent diversiform structures of POMs, the abundant metals and oxygen atoms in these inorganic clusters can not only supply metals, but can also provide the possibility for constructing porous architectures by releasing oxygen atoms during the pyrolysis process. Furthermore, there are advantageous synergistic effects when POMs are composited with other matrix precursors (such as polymers or carbon materials). On the other hand, the inherent heteroatoms of POMs can conveniently offer various kinds of heteroatom-doping (such as doping with P, Si, Ge, Se, or Sb) for the final electrode materials, which can further improve the electrochemical performances by their lone pair electrons or empty orbitals. Recently, such POM-derived electrode materials have attracted widespread attention primarily because of the convenient synthesis. This kind of effort provides the possibility to significantly alleviate the common problems of metal-based electrode materials, such as fast capacity decay, volume change, or phase transformation. In this review, the latest relevant research studies focusing on POM derivatives for rechargeable batteries are systematically summarized, including their syntheses, structures, electrochemical performances, and charge-storage mechanisms. Remarks on the challenges and future prospects of such POM-derived materials are also discussed and proposed, providing an emerging vision for the rational design and construction of novel electrode materials towards rechargeable batteries.